Tutorial: Designing Multi-projector VR Systems: From Bits to Bolts - Soares, L. P.; Jorge, J.; Dias, J.; Raposo, A.; Bruno R. de Araujo (Atas do EUROGRAPHICS 2010, 2010)
This tutorial will present how to design, construct and manage immersive multi-projection environments, covering everything from projection technologies to computer hardware and software integration. Topics such as tracking, multimodal interactions, and audio will be explored. In the end, we will present essential design decisions from actual cases. This tutorial introduces the issues to consider when planning to install a multi-projection environment for researchers and professionals in the field of computer graphics and virtual reality. No previous knowledge is necessary in the audience for the tutorial, except for basic knowledge of computer graphics and virtual reality.